2017
DOI: 10.1097/j.pain.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of neuropathic pain is high after treatment for breast cancer: a systematic review

Abstract: PROSPERO registration CRD42015029987.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…A prior systematic review of neuropathic pain after breast cancer surgery reported the prevalence ranged from 14% to 27%, based on the questionnaire used. 15 Our systematic review found a pooled prevalence of 29% for persistent neuropathic pain after surgery, and no evidence for a subgroup effect based on instrument-defined neuropathic pain (e.g. DN4, LANSS, or S-LANSS) vs clinically assessed neuropathic pain.…”
Section: Relation To Other Studies and Implicationsmentioning
confidence: 61%
See 1 more Smart Citation
“…A prior systematic review of neuropathic pain after breast cancer surgery reported the prevalence ranged from 14% to 27%, based on the questionnaire used. 15 Our systematic review found a pooled prevalence of 29% for persistent neuropathic pain after surgery, and no evidence for a subgroup effect based on instrument-defined neuropathic pain (e.g. DN4, LANSS, or S-LANSS) vs clinically assessed neuropathic pain.…”
Section: Relation To Other Studies and Implicationsmentioning
confidence: 61%
“…We screened the reference lists of all eligible studies and three previous systematic reviews for additional studies. 11,14,15 We included prospective and retrospective cohort or crosssectional studies that (i) enrolled 100 breast cancer patients and (ii) reported the prevalence or intensity of PPSP (3 months after surgery); Supplementary Appendix, section 1.2. We excluded conference abstracts, letters, and non-Englishlanguage articles.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…From the regression model, the DASH score showed statistically significant differences between the groups in that the neuropathic group demonstrated impaired upper limb function (P = 0.002). More important, the DASH score mean of 35 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in the nonneuropathic group versus 51 (41-67) in the neuropathic group met the minimum clinical important difference in change scores, indicating that these groups are not only statistically but also clinically different. 18 Due to the heavily skewed distribution of pain scores, the 11-point NPRS was analyzed based on percentages of those experiencing pain (NPRS 1 or higher) versus no pain.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic post-surgical neuropathic pain (NP, ICD 11 codes MG30.51 Chronic neuropathic pain after peripheral nerve injury and MG30.11 Chronic post cancer treatment pain) is common after breast cancer surgery with an estimated prevalence of 14-31% [1,2]. This condition may persist for years [3,4].…”
Section: Introductionmentioning
confidence: 99%